Sestrin2 induced by hypoxia inducible factor1 alpha protects the blood-brain barrier via inhibiting VEGF after severe hypoxic-ischemic injury in neonatal rats - Xudan Shi (Neurobiology of Disease, 2016)
Objective: Hypoxic ischemic (HI) encephalopathy remains the leading cause of perinatal brain injury resulting in long term disabilities. Stabilization of blood brain barrier (BBB) after HI is an important target, therefore, in this study we aim to determine the role of sestrin2, a stress inducible protein which is elevated after various insults, on BBB stabilization after moderate and severe HI injuries. Methods: Rat pups underwent common carotid artery ligation followed by either 150 min (severe model) or 100 min (moderate model) of hypoxia. 1 h post HI, rats were intranasally administered with recombinant human sestrin2 (rh-sestrin2) and sacrificed for infarct area, brain water content, righting reflex and geotaxis reflex. Sestrin2 was silenced using siRNA and an activator/inhibitor of hypoxia inducible factor1α (HIF1α) was used to examine their roles on BBB permeability. Results: Rats subjected to severe HI exhibited larger infarct area and higher sestrin2 expression compared to rats in the moderate HI group. rh-sestrin2 attenuated brain infarct and edema, while silencing sestrin2 reversed these protective effects after severe HI. HIF1α induced sestrin2 activation in severe HI but not in moderate HI groups. A HIF1a agonist was shown to increase permeability of the BBB via vascular endothelial growth factor (VEGF) after moderate HI. However, after severe HI, HIF1α activated both VEGF and sestrin2. But HIF1α dependent sestrin2 activation was the predominant pathway after severe HI which inhibited VEGF and attenuated BBB permeability. Conclusions: rh-sestrin2 attenuated BBB permeability via upregulation of endogenous sestrin2 which was induced by HIF1α after severe HI. However, HIF1α's effects as a prodeath or prosurvival signal were influenced by the severity of HI injury.